Two new species of the genus Myrsidea Waterston (Phthiraptera: Menoponidae) from cotingas (Passeriformes: Cotingidae) - Dalgleish, Robert C.; Price, Roger D. (Zootaxa, 2005)
Two new species of chewing lice of the genus Myrsidea Waterston from the passerine family Cotingidae are described and illustrated. They and their type host are: M. cinnamomei ex Pachyramphus cinnamomeus and M. blattae ex Schiffornis turdina. These are the first species of Myrsidea recorded from the Cotingidae.